Mechanical properties of toughened polyester reinforced with untreated and treated kenaf hybird carbon composite - Bonnia, Noor Najmi; Redzuan, Aein Afina; Surip, Siti Norasmah; Hassan, Noor Azlina (Scientific.Net, 2017)
This research focusing on mechanical properties of rubber toughened polyester filled carbon black (RPCB) reinforced with untreated kenaf (RPCBUK) and treated kenaf (RPCBTK). The samples were fabricated via compression moulding technique in which 3 % of LNR was added as toughening agent in this composite. Percentages of carbon black (CB) is 4 % and kenaf used vary from 5,10,15,20 and 25wt %. The mechanical properties were evaluated by impact and fracture toughness testing. The result for each test was discussed to determine the most optimum loading of kenaf fibre used to produce the best properties of composite. Untreated hybrid composite showed improvement on impact strength as compared to RPCB composite. RPCBTK with 25% of kenaf and RPCBUK with 5% of kenaf loading give the highest impact strength among the hybrid composites, approaching the strength of neat polyester. Same trend shows by fracture toughness testing. The microstructures of the composites’ fracture surface images from scanning electron microscope (SEM) prove the mechanical properties of the hybrid composites.